Experimental investigation of bio-concrete using eggshells as supplementary cementitious material - Abbas Ali; Jabr Elias (MATEC Web of Conferences)
The present experimental research study was focused on examining the feasibility of utilising recycled eggshells as a partial cement replacement in concrete, in order to provide a sustainable solution for the construction industry. The research work was carried out to examine the effects of substituting 15 %, 30 %, and 45 % of cement with eggshell powder on the physical and mechanical properties of concrete. This was mainly based on examining the fresh and hardened properties of eggshell concrete compared to ordinary Portland Cement (OPC) concrete. A series of tests including particle size distribution, compressive strength, workability, stiffness, setting time, and water absorption; were conducted to evaluate the performance of the modified concrete. The composition of the matrix was also examined using X-ray diffraction techniques (XRD). The results indicate that eggshell powder can serve as a viable partial replacement for cement, offering notable environmental benefits by reducing carbon emissions and waste, while maintaining acceptable levels of concrete performance. The findings of the study show that eggshell powder could contribute to more sustainable construction practices without compromising the structural integrity of concrete. This also enables the development of data-based guidelines for the uptake of an innovative and sustainable concrete product within the concrete industry.